Medieval Rus' and early modern Russia texts and contexts, essays in honour of Simon C. Franklin - Franklin, Simon 1953-; Torres Prieto, Susana; Franklin, Andrei (Routledge studies in the history of Russia and Eastern Europe, 2023)
List of figures -- List of contributors -- Foreword / by Andrei Franklin and Susana Torres Prieto -- List of abbreviations -- List of libraries and archives -- Leo VI and the transformation of Byzantine strategic thinking about the Rus' / Monica White -- Who was 'Theodore the Rhos from a family of emperors', the owner of the stone from the Holy Sepulchre? / Oleksiy Tolochko -- Cosmos, calendars and medical advice in the miscellanies of the Trinity Lavra of St. Sergius and their late Byzantine counterparts (14th-early 16th centuries) / Ann-Laurance Caudano -- Holy foolishness and gender transgression in Russian hagiography from the Middle Ages to modernity / Nick Mayhew -- Some unnoticed Greek quotes in old Russian Chronicles / Sergey A. Ivanov -- Retranslating the Rus' Primary Chronicle: perspectives on Horace Lunt's new rendering / Michael S. Flier -- Two emperors of the princess Olga's visit to Constantinople: Constantine VII Porphyrogenitos versus John Tzimiskes in the copies of the Rus' Primary Chronicle / Tatiana Vilkul -- Patriarch Germanus II of Constantinople and the Slavic world / Maria V. Korogodina -- Thoughtful agglomeration: late Byzantine sources for Muscovite ceremonial / Alexandra Vukovich -- Boris Godunov and his family in the mirror of medieval Russian polyonymy / Anna Litvina and Fjodor B. Uspenskij -- "I must be cruel only to be kind": towards a literary history of Kyiv graffito No. 108 / Aleksey A. Gippius -- Muscovite acquisition of books from Poland in the late 1640s-Early 1650s / Daniel C. Waugh and Olena Janssen -- The Codex in early Rus' between the 11th-15th centuries: variations of form and variations of function / Dmitrii Bulanin -- Sofiia Vitovtovna's dance: the wedding of Vasilii II in Russian cultural memory / Sergei Bogatyrev -- Revolution in the pictosphere: the Ukrainian Baroque and Muscovite reception / Valerie Kivelson -- Index.